Entrenamiento Para El Uso Del Baño - Millie Ferrer-Chancy; Sara McCrea (EDIS)
FCS2152-Span, a 3-page fact sheet by Millie Ferrer and Sara McCrea, is the Spanish version of "Toilet Training" (FSC2152) and will help parents understand when children are ready to start toilet-training, how to get the process started, and what to expect. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.